Estrutura, função e evolução das luciferases de Mastinocerini (Coleoptera: Phengodidae) e origem biossintética da luciferina em coleópteros - Souza, Daniel Rangel de (Universidade Federal de São Carlos, 2023)
The origin and evolution of bioluminescence in Coleoptera from the Elateroidea superfamily depend on a better understanding of the metabolic origin of the luciferin substrate and the luciferase enzymes evolution. Several luciferases from the 4 bioluminescent beetles families (Lampyridae, Elateridae, Phengodidae and Rhagophthalmidae) have already been cloned and investigated by our and other research groups in recent decades. However, only three functional luciferases from the Phengodidae family have been cloned and investigated so far, the red light-emitting luciferase from Phrixotrix hirtus head and the green light-emitting luciferase from Phrixotrix vivianii. Thus, the origin and evolution of head and lateral lanterns luciferases, as well as the relationship between structure and bioluminescence spectra in these enzymes, are still incomplete, needing to study other luciferases from different lanterns and life stages of other species that emit intermediate colors of light. Within this theme, this thesis had two main goals: (1) Increase knowledge of the bioluminescence evolution in the Phengodidae family through cloning, expression and characterization new active luciferases cDNA from different lanterns and (2) understand the biosynthetic origin of beetle luciferin. For the first time, we associate larva and adult of a phengodid specie, the Stenophrixotrix pallens found on the UFSCar Sorocaba campus, through molecular analyzes of the 16S and 18S rRNA genes and the bioluminescence spectra. We cloned two new luciferases cDNA, one from the Brasilocerus sp. head and another from P. hirtus lateral lanterns, we expressed them in bacteria and characterized these luciferases. Luciferase from Brasilocerus sp. head lantern presented a peak of bioluminescent emission at 566 nm in pH=8, while the luciferase from the P. hirtus lateral lanterns shows an emission peak at 563 nm. The presence of a single luciferase in the head and lateral lanterns trascriptomes of Brasilocerus sp., the kinetic and spectral characteristics of luciferass from Stenophrixotrix pallens larvae, suggest for the first time that some species of Mastinocerini presente only one luciferase isoform in different lanterns and life stages, unlike Phrixotrix spp. The R215T mutation and the asparagine 351 deletion in the P.hirtus lateral lanterns luciferase had a bathochromic efect of ~30 nm, confirming the importance of arginine 215 and loop 351-360 in bioluminescence spectra determination. Finally, to better understand the biosynthetic origin of luciferin in coleopterans, we developed bioluminescent bacteria transformed with Amydetes vivianii luciferase to evaluate the in vivo synthesis of luciferin in the presence of cystein and quinine precursors. These studies showed that cysteine has a detoxifying impact on p-benzoquinone concomitantly with luciferin formation, suggesting that coleopteran luciferin may have arisen as a by-product of quinone detoxification.
Structure, function, and evolution of luciferases from Mastinocerini (Coleoptera: Phengodidae) and luciferin biosynthetic origin in coleoptera
Keywords: Bioluminescência; Fengodídeos; Luciferases; Luciferina; Bioluminescence; Phengodidae; Luciferin; CIENCIAS BIOLOGICAS::BIOQUIMICA::BIOLOGIA MOLECULAR